Effects of differential strategies of emotion regulation - Böhme, Stephanie; Biehl, Stefanie C.; Muehlberger, Andreas (Brain Sciences, 2019)
Patients suffering from mental disorders, especially anxiety disorders, are often impaired by inadequate emotional reactions. Specific aspects are the insufficient perception of their own emotional states and the use of dysfunctional emotion regulation strategies. Both aspects are interdependent. Thus, Cognitive Behavioral Therapy (CBT) comprises the development and training of adequate emotion regulation strategies. Traditionally, reappraisal is the most common strategy, but strategies of acceptance are becoming more important in the course of advancing CBT. Indeed, there is evidence that emotion regulation strategies differ in self-reported effectiveness, psychophysiological reactions, and underlying neural correlates. However, comprehensive comparisons of different emotion regulation strategies are sparse. The present study, therefore, compared the effect of three common emotion regulation strategies (reappraisal, acceptance, and suppression) on self-reported effectiveness, recollection, and psychophysiological as well as electroencephalographic dimensions. Twenty-nine healthy participants were instructed to either reappraise, accept, suppress, or passively observe their upcoming emotional reactions while anxiety-and sadness-inducing pictures were presented. Results showed a compelling effect of reappraisal on emotional experience, skin conductance response, and P300 amplitude. Acceptance was almost as effective as reappraisal, but led to increased emotional experience. Combining all results, suppression was shown to be the least effective but significantly decreased emotional experience when thoughts and feelings had to be suppressed. Moreover, results show that greater propensity for rumination differentially impairs strategies of emotion regulation.
Created from Fastlane, Scopus look-up
Keywords: Electroencephalography; Emotion regulation; Skin conductance response